Genesis of a Fact: Tay-Sachs Disease as a “Simple Recessive” - Lubinsky, Mark (Journal of Pediatric Genetics, 2023)
“Obvious” recessive inheritance of Tay-Sachs disease (TSD; OMIM # 272800) took over half a century to be established. Points now taken for granted were problematic, that: (1) TSD is a biological entity, not an artificial selection of concurrent findings, (2) manifestations have narrow limits, (3) it was not part of a spectrum of disorders, and can be differentiated from other conditions, (4) it will not change to another disease, (5) it is due to a single specific gene, (6) there are no secondary causes, (7) the gene has no apparent clinical effects unrelated to TSD, and (8) the gene is inherited only as a clinical recessive. To a large extent, resolution reflected biochemical understanding that took until mid-20th century, and beyond, to change how physicians viewed diseases in general. With this, biochemical carrier screening and prenatal biochemical diagnosis have become routinely available, and it is a model for carrier population screening, while gene therapy for the disease has been reported with some degree of success. Here, the history of medical ideas about TSD and its inheritance are reviewed to show how it achieved its current status as a distinct recessive disorder.
Keywords: genetics; heredity; neuropathic inheritance; recessive inheritance; Tay-Sachs disease